Saffron harvestability detection with deep neural networks for just-in-time harvesting - Carter T. Noh; Nathan Jones; Douglas D. Cook (Biosystems Engineering, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Bipolar volcanic ice-core synchronization of the entire last glacial period - Anders Svensson; Guido Vettoretti; Jia-mei Lin; Giulia Sinnl; Dorthe Dahl-Jensen; Jørgen Peder Steffensen; Sune Olander Rasmussen; Bo Vinther; Christine Hvidberg; Helle Astrid Kjær; Vasileios Gkinis; Eliza Cook; et al. (Quaternary Science Reviews, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Rethinking adaptation interventions in agricultural systems for sustainability - Sechindra Vallury; Donald R Nelson; Nathan J Cook (Current Opinion in Environmental Sustainability, 2025)

Interpreting field measurements of juvenile growth and survival rates with population growth isoclines - Nathan T. Barrus; Mark I. Cook; Nathan J. Dorn (Ecology, 2025)
Juvenile survival and growth rates are commonly studied demographic rates with consequences for population growth. For species that can achieve a size refuge from juvenile predators, the time spent at smaller vulnerable sizes is expected to affect population dynamics. But the interactive effects of juvenile growth and survival on population growth are rarely illustrated theoretically, and most studies of these concepts have been in experimental settings. The interactive effects of the two rates have applications to field studies of recruitment variation for a diversity of species that could be assessed with demographic models and isoclines. We conceptually illustrate the potential use of demographic isoclines for marine, terrestrial, and freshwater examples in the literature, and then demonstrate the use of a demographic isocline for an annual freshwater gastropod (Florida Apple Snail, Pomacea paludosa ). Using a published size‐indexed demographic model, we constructed a zero‐population growth isocline for theoretical combinations of juvenile growth and survival rates. We then quantified daily juvenile survival and growth in two wetlands twice during the recruitment period, incorporating variable predator assemblages and seasonal environmental conditions (i.e., water depth and temperature). Daily juvenile survival rates were lower in the cooler dry season and juvenile growth was faster in the warmer wet (rainy) season. Parameter combinations of juvenile growth and survival in the dry season predicted declining populations (λ

Forty-five years of removal campaigns for feral ungulates reveal strategies for success and future directions - Nathan P. Snow; Keely J. Kohen; Ingrid A. Messer; Abigail Pagels; Seth M. Cook; Scott Beckerman; Travis Guerrant; Kurt C. VerCauteren; Kim M. Pepin (Biological Invasions, 2025)
Feral or invasive ungulates (hereafter: feral ungulates) exist worldwide, and their ability to thrive threatens biodiversity, degrades ecosystems, and causes damage to agriculture and properties. Strategies for removing feral ungulates from their introduced insular and mainland ranges have varied greatly, successes have been difficult, and the need is increasing. We reviewed published scientific literature on feral ungulate eradication and maximum control campaigns during 1978–2023 to identify practices that led to greater success. Of 54 campaigns, 32 (59%) reported success. Most campaigns focused on feral swine (61%; Sus scrofa ) or feral goats (24%; Capra hircus ). The average duration of a campaign was 61 months and cost an average of $1.9 m ($USD 2024) or $636/km 2 /month. The most important components for success included ensuring adequate funding was secured for the campaign ($0.5–1 million/km 2 is recommended) and population recovery or reinvasion were minimized. The frequency of campaigns has increased during the last 45 years; however, the areas worked (km 2 ), monthly durations, removal techniques used, funding, and ultimately the rates of success have not changed. A lack of increasing success for larger and more complex campaigns indicated that modernization of technologies for population control has been minimal, and larger breakthroughs are needed. Safe and effective toxicants and sterilants may provide those advances if developed. Lessons learned from campaigns indicate that pilot testing control methods prior to initiating full campaigns may help to alleviate uncertainties, produce more reliable plans, and help inform the biology of the animals being targeted for removal.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Comparing efficiencies of population control methods for responding to introductions of transboundary animal diseases in wild pigs - Nathan P. Snow; Benjamin Smith; Michael J. Lavelle; Michael P. Glow; Kayleigh Chalkowski; Bruce R. Leland; Sarah Sherburne; Justin W. Fischer; Keely J. Kohen; Seth M. Cook; Hatton Smith; Kurt C. VerCauteren; et al. (Preventive Veterinary Medicine, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Diverting Food Waste From Landfill in Exemplar Hospital Foodservices: A Qualitative Study - Nathan Cook; Judi Porter; Denise Goodwin; Jorja Collins (Journal of the Academy of Nutrition and Dietetics, 2024)

What is known, unknown, and needed to be known about damage caused by wild pigs - Kurt C. VerCauteren; Kim M. Pepin; Seth M. Cook; Sophie McKee; Abigail Pagels; Keely J. Kohen; Ingrid A. Messer; Michael P. Glow; Nathan P. Snow (Biological Invasions, 2024)
Damage assessments provide evidence for initiating and evaluating management programs that protect natural resources and human livelihoods against invasive species. Wild pigs ( Sus scrofa ) cause extensive damage in their native and non-native ranges, but the extent of current damage and efficacy of management of the damage (i.e., population control of wild pigs, exclusion fencing, etc.) remains poorly described. We conducted a systematic review of physical damage caused by wild pigs to summarize what is known and identify knowledge gaps for damage assessment. Wild pig damage assessments have been overwhelmingly qualitative (84% of studies) and measured differently across studies, which prevents the determination of typical damage amounts to a particular resource and comparison across studies. Key priorities going forward are to standardize damage assessments quantitatively and measure population density (or index of such) of wild pigs concurrently with damage assessments to determine the relationship between damage and population levels. We provide a framework for inferring damage in new areas and assessing the benefits of management—to evaluate and optimize landscape-scale management programs. Overall, we recommend future studies strive for: (1) report the amount of damages in a standardized fashion (e.g., area damaged/area surveyed), (2) evaluate and report the amount of damage relative to the density of wild pigs, and (3) when reporting economic costs of damages incurred and management actions, describe the economic valuation method used along with the year of reference for the valuation. Capturing these elements are necessary steps to predict the benefits of management for an area with particular profile of resources and wild pig density, even in areas where damage assessments are not available. Meeting these criteria with allow for more generalizable results that can inform managers across the nearly global distribution of wild pigs.

Mid-to Late Holocene East Antarctic ice-core tephrochronology: Implications for reconstructing volcanic eruptions and assessing their climatic impacts over the last 5,500 years - Peter M. Abbott; Joseph R. McConnell; Nathan J. Chellman; Sepp Kipfstuhl; Maria Hörhold; Johannes Freitag; Eliza Cook; William Hutchison; Michael Sigl (Quaternary Science Reviews, 2024)

Experimental evidence on minority participation and the design of community-based natural resource management programs - Nathan J. Cook (Ecological Economics, 2024)

Spatial variation in spawning timing for multi-species Acropora assemblages in the Red Sea - Eslam O. Osman; David J. Suggett; Tamer M. Attalla; Marco Casartelli; Nathan Cook; Islam El-Sadek; Ahmed Gallab; Elizabeth A. Goergen; Neus Garcias-Bonet; Jessica S. Glanz; Pedro Henrique Pereira; Megan Ramirez-Sanchez; et al. (Frontiers in Marine Science, 2024)
Sexual reproduction is a crucial process for reef building coral populations to maximize genetic diversity and recover from large scale disturbances. Mass spawning events by Acropora species represent critical opportunities for populations to persist, and a process that is increasingly exploited to actively restore degraded reefs. However, the timing and predictive capacity of coral spawning throughout the broad thermal and environmental regime of the Red Sea – a region also undergoing significant development and active reef restoration – remains patchy. We, therefore, conducted three parallel reef surveys in the central Red Sea (Al-Fahal Reef, Thuwal - Saudi Arabia) and the eastern (Shushah Island - Saudi Arabia) and western (Hurghada – Egypt) coast of the northern Red Sea. Surveys assessed the gravidity of gonads, spawning timing, alignment with the lunar cycle of 21 Acropora spp. (total n= 572 colonies) around the full moons of April and May 2023. Consistent with past observations, synchronous spawning was observed for Acropora spp. in both the central and northern Red Sea during April and May, respectively. Interestingly, corals spawned on the full moon in both Shushah and Thuwal sites. In contrast, corals in Hurghada were independent of the lunar cycle and spawned 7-9 nights before the full moon in May. By integrating our 2023 observations with the historical spawning events in Hurghada and Thuwal (2002-2022), we found that the deviation of spawning timing from the full moon day was correlated with absolute Sea Surface Temperature (SST) (earlier spawning before the full moon day, lower SST) and warming rate (earlier spawning, more rapid warming) in 6-weeks prior to spawning. As such, temperature pattern is likely one of the primary factors governing gamete release, among other factors, that likely influence spawning day within the lunar month. These correlations between SST metrics and spawning timing suggest a potential framework to predict future Acropora spp. spawning dates. Our observations demonstrate the importance of parallel efforts across borders to collect critical data needed to inform management strategies aimed at conserving and restoring coral reefs in this ecologically diverse region.

Examining the effects of soil entrainment during nuclear cloud rise on fallout predictions using a multiscale atmospheric modeling framework - Katherine A. Lundquist; Robert S. Arthur; Stephanie Neuscamman; Joseph P. Morris; Christian R. Scullard; Andrew W. Cook; Nathan G. Wimer; Peter Goldstein; Gregory D. Spriggs; Lee G. Glascoe; John S. Nasstrom (Journal of Environmental Radioactivity, 2023)

Corrigendum to “Evaluation of the impact of aquatic-animal excretion on nutrient recycling and retention in stormwater treatment wetlands” [Ecological Engineering 197 (2023) 1–20/107104] - Mark B. Barton; Janelle A. Goeke; Nathan J. Dorn; Mark I. Cook; Susan Newman; Joel C. Trexler (Ecological Engineering, 2023)

Evaluation of the impact of aquatic-animal excretion on nutrient recycling and retention in stormwater treatment wetlands - Mark B. Barton; Janelle A. Goeke; Nathan J. Dorn; Mark I. Cook; Susan Newman; Joel C. Trexler (Ecological Engineering, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Life history responses of two co-occurring congeneric Apple Snails (Pomacea maculata and P. paludosa) to variation in water depth and metaphyton total phosphorus - Nathan T. Barrus; Danielle Drumheller; Mark I. Cook; Nathan J. Dorn (Hydrobiologia, 2023)

Promoting women’s leadership under environmental decentralization: The roles of domestic policy, foreign aid, and population change - Nathan J. Cook; Michelle E. Benedum; Ganesh Gorti; Sitashma Thapa (Environmental Science & Policy, 2023)

Engineering, Ecological and Social Monitoring of the Largest Underwater Sculpture in the World at John Brewer Reef, Australia - Adam Smith; Al Jayson Songcuan; Nathan Cook; Rachelle Brown; Kailash Cook; Reuben Richardson (Journal of Marine Science and Engineering, 2022)
The largest underwater sculpture in the world, the ‘Coral Greenhouse’ by artist Jason deCaires Taylor, was commissioned by the Museum of Underwater Art and installed at John Brewer Reef, Australia, in December 2019. The planning process required certified engineering design drawings associated with design life, durability and suitability of materials, and baseline ecological surveys. Following approval, the operational phase required annual monitoring of substrate, ecology, social values, and marine debris. We geo-referenced three permanent transects and designed a before/after rapid monitoring assessment of substrate, fish, and invertebrates. Substrate surveys indicated 11% concrete and 89% sand. Fish surveys indicated significant increases of diversity and abundance, with 12 species and 65 individuals recorded in 2018 compared to 46 species and 365 individuals recorded in 2022. Macroinvertebrate species maintained no significant trends in abundance, species richness, and diversity with respect to time between 2018 and 2022. We monitored coral restoration and natural recruitment at the site, measuring aesthetics, survivorship of planted corals, and coral recruitment. Of 131 corals transplanted in March 2020, survivorship was 100% at 1 month, 92% at 6 months, and 91.6% at 12 months. Hard and soft corals were recruited to the structure at a density of 8.35 hard corals/m2 and 10.9 soft corals/m2 over 26 months.

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

The role of direct chemical inhibition in the displacement of a native herbivore by an invasive congener - Danielle K. Drumheller; Mark I. Cook; Nathan J. Dorn (Biological Invasions, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Hydrological disturbance diminishes predator control in wetlands - Nathan J. Dorn; Mark I. Cook (Ecology, 2015)
Effects of predators on prey populations can be especially strong in aquatic ecosystems, but disturbances may mediate the strength of predator limitation and even allow outbreaks of some prey populations. In a two‐year study we investigated the numerical responses of crayfish ( Procambarus fallax ) and small fishes (Poeciliidae and Fundulidae) to a brief hydrological disturbance in replicated freshwater wetlands with an experimental drying and large predatory fish reduction. The experiment and an in situ predation assay tested the component of the consumer stress model positing that disturbances release prey from predator limitation. In the disturbed wetlands, abundances of large predatory fish were seasonally reduced, similar to dynamics in the Everglades (southern Florida). Densities of small fish were unaffected by the disturbance, but crayfish densities, which were similar across all wetlands before drying, increased almost threefold in the year after the disturbance. Upon re‐flooding, juvenile crayfish survival was inversely related to the abundance of large fish across wetlands, but we found no evidence for enhanced algal food quality. At a larger landscape scale (500 km 2 of the Everglades), crayfish densities over eight years were positively correlated with the severity of local dry disturbances (up to 99 days dry) during the preceding dry season. In contrast, densities of small‐bodied fishes in the same wetlands were seasonally depressed by dry disturbances. The results from our experimental wetland drought and the observations of crayfish densities in the Everglades represent a large‐scale example of prey population release following a hydrological disturbance in a freshwater ecosystem. The conditions producing crayfish pulses in the Everglades appear consistent with the mechanics of the consumer stress model, and we suggest crayfish pulses may influence the number of nesting wading birds in the Everglades.

Zooplankton dynamics in response to the transition from drought to flooding in four Murray–Darling Basin rivers affected by differing levels of flow regulation - Nathan S. P. Ning; Ben Gawne; Robert A. Cook; Daryl L. Nielsen (Hydrobiologia, 2013)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Predicting phenology by integrating ecology, evolution and climate science - Stephanie Pau; Elizabeth M. Wolkovich; Benjamin I. Cook; T. Jonathan Davies; Nathan J. B. Kraft; Kjell Bolmgren; Julio L. Betancourt; Elsa E. Cleland (Global Change Biology, 2011)
Forecasting how species and ecosystems will respond to climate change has been a major aim of ecology in recent years. Much of this research has focused on phenology – the timing of life‐history events. Phenology has well‐demonstrated links to climate, from genetic to landscape scales; yet our ability to explain and predict variation in phenology across species, habitats and time remains poor. Here, we outline how merging approaches from ecology, climate science and evolutionary biology can advance research on phenological responses to climate variability. Using insight into seasonal and interannual climate variability combined with niche theory and community phylogenetics, we develop a predictive approach for species’ reponses to changing climate. Our approach predicts that species occupying higher latitudes or the early growing season should be most sensitive to climate and have the most phylogenetically conserved phenologies. We further predict that temperate species will respond to climate change by shifting in time, while tropical species will respond by shifting space, or by evolving. Although we focus here on plant phenology, our approach is broadly applicable to ecological research of plant responses to climate variability.